Learning Assemblages - McFarlane, Colin (Learning the City: Knowledge and Translocal Assemblage, 2011)
This chapter contains sections titled: Introduction Translation: Distribution, Practice and Comparison Coordinating Learning Dwelling and Perception Assemblage Space Conclusion